“Effect Of Lung Flute And Musical Flute Therapy With Conventional Chest Physiotherapy Among Bypass Graft Patients: An Experimental Study” - Pratibha; Dr.Deepak Raghav; Dr.Bhawna (Revista Electronica de Veterinaria, 2024)
Background: Pulmonary complications after bypass-grafting surgery are usually seen in patients who have a very long period of immobility and under anaesthesia followed by surgical stress. Traditional chest physiotherapy (CCPT) remains the most widely accepted form of treatment for such conditions. Still, with emerging adjuncts like lung flute and musical flute therapy, additional measures can now enhance respiratory function recovery processes. Lung flute therapy uses sound vibrations to loosen mucus and thus improves airway clearance, while musical flute uses combination of controlled breathing and emotional relaxation to improve the strength of lung capacity. This study aims to compare the efficacy of lung flute therapy, musical flute therapy, and conventional chest physiotherapy in improving respiratory outcomes among bypass graft patients. Methods: This randomized control trial involved recruiting 90 patients who had undergone CABG surgery and randomizing them into three groups: (1) Lung Flute Therapy (LFT), (2) Musical Flute Therapy (MFT), and (3) Conventional Chest Physiotherapy (CCPT). Interventions were carried out twice a day over two weeks following surgery. Pre-and post intervention results were collected for pulmonary function tests (PFTs), including forced expiratory volume (FEV1), forced vital capacity (FVC), and peak expiratory flow rate (PEFR). Moreover, subjective measures involving dyspnoea scale scores as well as quality of life (QOL) reported by patients were explored. Results: At the conclusion of the two-week intervention, all the three groups demonstrated statistically significant enhancements in PFTs and QOL scores (p < 0.05). The extent of improvement, however, was group dependent. Conclusion: Musical flute and lung flute therapy as adjuncts to physical chest therapy gives significant gains in respiratory recovery for patients who have been subjected to CABG surgery. Lung flute is mucus clearance and patency in the airway, while musical flute therapy induces relaxation and good functionality of the lungs. Therefore, the two therapiesprovidecomplementaryadvantagestoCCPTandmightbeusedasadjunctstherapyoptions within the pulmonary rehabilitation protocols set for bypass graft patients. These outcomes need to be validated with larger sample sizes and long-term benefits studies.